Research conducted in an international company with the aim to determine managers effect on employees' stress levels, their intention to resign, and commitment to the organization - (:unkn) unknown (ARDABIL INDUSTRIAL MANAGEMENT INST, 2017)
The purpose of this study is to identify the extent of manager's effect on employees' stress levels, their intention to resign and commitment to the organization. The research is descriptive and correlation analysis has been used. Upon examination of 652 surveys, it becomes clear that managers have direct impact on employees' various perceptions of the job. This research highlights the importance of correct managerial skills in shaping a positive business enviromnent for employees. (C) AIMI Journals
Keywords: Organizational Stress; Organizational Commitment; Intention to Resign; Employee Satisfaction